The mining industry and the societal evolutions : what are the impacts of the expectations of the populations and local authorities on the development of the mining projects? - (:unkn) unknown (My University, 2014)
Since the beginning of the 1990s, almost throughout the world, bordering communities of mining projects oppose the proceedings of mining exploitation works. This phenomenon occurs in developed countries as well as in developing countries. It is also present both in democratic and in non democratic countries.To justify the determination to offer solutions to this problem, the first part of this work proves that the mining industry is the catalyst and the base of the modern economic growth and that, consequently, any disturbance in the safety of mining product supplying deserves a mobilization of the international community.In the second part, the conclusion shows that these mistrust actions are far from being ideological claims. They are simply the expression of a contemporary request which consists in integrating into mining resource development decisions the principles globalization is based on : the respect for the right to collective and individual development, the respect for human rights, including the right to the environment and the participation of communities or individuals in any decision-making that may affect their lives.In the third part, it is proved that the African continent has turned to be the new mining development pole since the end of the cold war. In these conditions, the study of the issue of the community mobilizations against mining exploitation, in four African countries with strong mining traditions such as Guinea and Morocco and in the process of mining development such as Mali and Ivory Coast, allows us to understand that mobilizations against mining projects do really exist in Africa.In these conditions and as a conclusion, it is first of all necessary to wish that the international community be concerned by this issue to organize a world summit on the future of the mining industry in the 20th century, and that a World Fund in the service of the Development of Communities Concerned by Mining Projects (FMDCAPM) be created.S
Keywords: African Research